Transaction costs of forest carbon projects - Milne, M. (University of New England, 2002)
This report provides some preliminary estimates of transaction costs, especially to project developers and investors and outlines the steps involved in establishing and implementing a number of forest-carbon projects. In order to provide more comprehensive policy recommendations on how to minimise transaction costs, more analysis is required on the distribution of transaction costs between the stakeholders. Currently, this type of study is constrained by the lack of an international carbon market, the early stages at which most projects are, and the limited number of forest-carbon projects in operation. As the carbon market develops, more operational entities are likely to enter, resulting in reduced transaction costs for individual projects. In terms of the size of transaction costs in the carbon market, this will depend on the institutional capacity and policy environment of both project type (annex 1) and host countries, and the establishment of new institutions to provide services currently implemented by individual projects and their partners.